2020
DOI: 10.1186/s12883-020-01821-1
|View full text |Cite
|
Sign up to set email alerts
|

Two case reports of distal upper limb weakness following influenza-like illness: an emerging pattern of para-infectious myositis in adults

Abstract: Background: Myositis is a recognised complication of numerous systemic viral infections including influenza. In adults the typical pattern is characterised by myalgia and marked proximal muscle weakness in upper and lower limbs and resolves slowly over weeks rather than days. Case presentation: Here, we describe two male patients with myositis with an unusual distribution of weakness in the distal upper limbs, which both followed a flu-like illness and resolved spontaneously. Both patients had moderate elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…24 These cases present with a prodromal phase of myalgia followed by involvement of variable patterns of muscle distribution of both upper and lower limbs. 9 The clinical presentation of our case does not t with any of the known subgroups of myositis detailed in Table 1. It lacks the systemic involvement of DM, not typical clinical features of ADM, not the typical proximal distribution of PM, no drug history to suggest NM or the typical age of JM.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…24 These cases present with a prodromal phase of myalgia followed by involvement of variable patterns of muscle distribution of both upper and lower limbs. 9 The clinical presentation of our case does not t with any of the known subgroups of myositis detailed in Table 1. It lacks the systemic involvement of DM, not typical clinical features of ADM, not the typical proximal distribution of PM, no drug history to suggest NM or the typical age of JM.…”
Section: Discussionmentioning
confidence: 67%
“…Scaber et al suggested an emerging pattern of para-infectious myositis in adults. 9 They described acute myositis in two male patients with an unusual distribution of weakness in the distal upper limbs, which both followed a u-like illness and resolved spontaneously. The rst case was 38 and the second was 54 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral upper extremity weakness, and bilateral hand weakness due to myositis, and bilateral femoral nerve compression due to rhabdomyolysis have been reported. [5][6][7] Although incidence of neurological complications is not definitely known it is predicted to be 4 per 100,000 children in a year. 1 There is no marker to predict the development of neurological complications in patients with influenza-like symptoms.…”
Section: Discussionmentioning
confidence: 99%